Early approval of COVID-19 vaccines: Pros and cons - Md Arifur Rahman; Md Sayeedul Islam (Taylor & Francis Group, 2021)
The development of safe and effective vaccines has been an overriding priority for controlling the 2019-coronavirus disease (COVID-19) pandemic. From the onset, COVID-19 has caused high mortality and economic losses and yet has also offered an opportunity to advance novel therapeutics such as DNA and mRNA vaccines. Although it is hoped that the swift acceptance of such vaccines will prevent loss of life, rejuvenate economies and restore normal life, there could also be significant pitfalls. This perspective provides an overview of future directions and challenges in advancing promising vaccine platforms to widespread therapeutic use.